Carga de trabalho de enfermagem e infecções relacionadas à assistência à saúde na unidade de terapia intensiva - Elias, Tatiana Maria Nóbrega (2012)
In recent decades, the search for quality care has been widely discussed by the institutions and health professionals. In this context, it is the nurse coordinator of the process of providing nursing staff, reflecting the commitment to quality of care. In this process, it is the appearance of Infections Related to health care and its potential association with the workload in nursing as a valuable indicator of quality of care. Thus, this research contributes to studies to characterize the demand of nursing work to promote a safe healthcare practice. This study aimed to identify the association of nursing workload with the number of cases of Ventilator-Associated Pneumonia, urinary tract infection and central venous catheter infection in the intensive care unit. This is a quantitative research approach, descriptive, cross-sectional and prospective, held at Unimed Hospital in Natal-RN. The study population consisted of all patients treated in the Intensive Care Unit, Hospital for a period of 90 consecutive days in 2011. The convenience sample was compostapelos patients admitted to the ICU during the period of data collection, a total sample of 286 patients. To perform the data analysis software were used: Statistica 6.0, SPPS (Statistical Package for Social Sciences) version 17.0 (2004) and Excel 2007. In the descriptive analysis, we used Measures of Central Tendency and Measures of Dispersion or Variability and the use of nonparametric tests. Of the 286 patients, 88 were from the ICU and 198 ICU II II. Males predominated in the ICU I (51.1%) and female ICU II (57.6%) patients in the ICU I were aged 61-80 years (39.8%) followed by greater than 80 years (39.8%). In the ICU II, most of the patients were aged 61-80 years (38.9%) and then from 41 to 60 years (24.2%). In relation to the class of TISS inlet predominant class II in the two ICUs (59.1%), followed by Class III also in the two units (34.6%). Most patients (70.6%) out of the ICUs belonging to class II TISS. In the ICU I, the average number of forms of the TISS 28 was 6, has in ICU II this value drops to 3.2 forms. The overall mean was 19.9 TISS points in ICU patients I and ICU II.the 17 points in the average hours required to provide adequate nursing care to patients in the ICU I found that is 10 , 7 hours, and the ICU II 9.2 hours. It was found that the time provided by the nursing staff were higher in ICU II, with an average of 19 hours available for nurses in this sector. In the ICU I, which showed higher need of available hours, it was found that the mean value of 12.7 available hours. It was found that only 2.4% of patients had these units Ventilator-Associated Pneumonia, 1.0% were infected central venous catheter and 1.4% of patients had urinary tract infection. Infection associated with health care occurs, on average, on the tenth day of hospitalization. In the ICU II, this average value extends to the twelfth day with an excess of 2.7 hours of nursing care while in ICU I value decays to the ninth day of hospitalization with a deficiency of 12-hour assistance. It is concluded that patients generally showed a need for classification of semi-intensive care and has been assisted in their need to load. As for his association with the Related Infections Health will assist this analysis could not be performed due to the small number of notifications in this period. It is suggested further study how other factors related to infections me a longer period of analysis